2019
DOI: 10.1002/jat.3831
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cannabidiol on male reproductive system: A literature review

Abstract: Cannabidiol (CBD) is one of the most abundant phytocannabinoids present in the plant Cannabis sativa (marijuana). There have been several studies of CBD in the last few decades, mainly focused on its neuroprotective properties, particularly after the identification of the endocannabinoid system and its participation in the central nervous system. On the other hand, the peripheral effects of CBD, particularly on reproductive physiology, were also evidenced. A narrative review was conducted using the PubMed data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 107 publications
0
24
0
Order By: Relevance
“…Alterations of testosterone production were substantiated by in vitro data on rat testicular microsomes, which demonstrate inhibition of the steroidogenic enzyme progesterone 17-a hydroxylase. Similar studies in rat liver microsomes suggested that CBD exposure could also alter hepatic metabolism of sex steroids (as reviewed in Carvalho et al, 2020).…”
Section: Hypothalamic-pituitary-gonadal Axismentioning
confidence: 67%
“…Alterations of testosterone production were substantiated by in vitro data on rat testicular microsomes, which demonstrate inhibition of the steroidogenic enzyme progesterone 17-a hydroxylase. Similar studies in rat liver microsomes suggested that CBD exposure could also alter hepatic metabolism of sex steroids (as reviewed in Carvalho et al, 2020).…”
Section: Hypothalamic-pituitary-gonadal Axismentioning
confidence: 67%
“…Pre-clinical studies, carried out on animal models, reported acute and chronic adverse effects of CBD on different organs and systems ( Table A2 ) [ 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ]. There are several highly recommended comprehensive reviews, which critically analyzed the CBD safety and toxicity experiments carried out in animal pre-clinical and human clinical trials [ 53 , 123 , 124 , 125 , 126 , 127 ]. The following important observations should be mentioned: (1) regarding the administration route, in most human trials, CBD was administrated orally or by inhalation, whereas predominantly intraperitoneal (i.p.)…”
Section: Cbd Tolerability Toxicity and Adverse Effectsmentioning
confidence: 99%
“…caused acute CNS toxicity (tremor, sedation, and prostration) within 30 min of injection, whereas prolonged treatment for 9 days elicited bradycardia, hypopnea, cardiac failure, liver weight increase, and inhibition of spermatogenesis [ 113 , 125 ]. For the same model (rhesus monkeys), chronic oral CBD application (30–300 mg/kg/day, 90 days) caused systemic negative effects on the liver, heart, kidneys, and thyroids, and inhibited spermatogenesis [ 113 , 124 , 125 ]. Negative effects of chronic CBD on embryonic development were reported in rats when relatively high doses (75–250 mg/kg/day) were administrated orally during pregnancy, which included developmental toxicity, decreased fetal body weight, increased fetal structural variations, and embryofetal mortality [ 125 ].…”
Section: Cbd Tolerability Toxicity and Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…or oral gavage (p.o.) to assess the physiological and/or toxicological effects of cannabis (Carvalho et al, 2020). Approximately 120 unique phytocannabinoids are present in Cannabis sativa (Cather and Cather, 2020) and can vary depending on the cannabis chemovars.…”
Section: Introductionmentioning
confidence: 99%